BAHTSUL MASAIL DAN KITAB KUNING DI PESANTREN - Anam, Ahmad Khoirul (INC- Islam Nusantara Center, 2018)
Bahtsul masail is one of the mechanisms of Islamic jurisprudence in Indonesia which is done collectively (jama’ i). Forum that comes fromthis pesantren is not consisted of permanent council, but open to kiai and jurisprudence. The term bahtsul masail itself comes from pesantren, which is a substitute for the word ijtihad or istinbath. Bahtsul masail can also be referred to as intellectual forum of pesantren outside the learning system. In the tradition of pesantren learning, the students studied the yellow book with sorogan and bandongan system. In the sorogan tradition, the santri individually get direct guidance from the kiai or ustadz. While in the bandongan system the santri together listened to the reading and explanation of the kiai while giving notesto their respective books. While the mass bahsul masail in pesantren is a higher-level recitation system, involving senior santri who have met certain scientific standards, or alumni who have completed the education phase at the pesantren. In this issue the senior students and alumni of pesantren are ‘challenged’ to think hard and solve various religious problems faced by the surrounding community with the reference of ‘kitab kuning’ that have been studied. Bahtsul masail not only serves as a forum for discussion or assessment forums, more than that bahtsul masail becomes a forum of legal determination on some importantissues concerning the problematic of people from time to time. When it was adopted by Nahdlatul Ulama (NU) since the founding of the organization in 1926, bahtsul masail has grown, both in terms of the choice of masail (question), as well as its procedures of discussion and ratification; according to the development flow of NU organization from year to year. It can be simply said that the first bahtsul masail was a forum to seek the reference of various religious questions (masa’il diniyyah) from collective kitab kuning (jama’ i).